[PP.16.08] AN ASSESSMENT OF THE ACCURACY OF HOME BLOOD PRESSURE MONITORS WHEN USED IN DEVICE OWNERS. (September 2017) - Padwal, R.; Polley, G.; McLean, D.; Thompson, A.; Morales, F.; Ringrose, J.
Abstract : Objective: To examine the accuracy of home BP devices when used in device owners compared to the auscultatory reference standard Design and method: Eighty-five consecutive consenting subjects 18 years of age or greater, who owned an oscillometric home BP device (wrist or upper-arm device), with BP levels between 80–220/50–120 mmHg, and with arm circumferences between 25–43 cm were studied. Pregnancy and atrial fibrillation were exclusion criteria. Device measurements from each subject's home BP device were compared to simultaneous two-observer auscultation using a mercury sphygmomanometer. Between-group mean comparisons were conducted using paired t-tests. The proportion of patients with device-to-auscultatory differences of 5, 10 and 15 mmHg or greater were tabulated and predictors of systolic and diastolic BP differences were identified using linear regression. Results: Mean age was 66.4 ± 11.0 years, mean arm circumference was 32.7 ± 3.7 cm, 54% were female and 78% had hypertension. Mean BPs were 125.7 ± 14.0/73.9 ± 10.4 mmHg for home BP devices versus 129.0 ± 14.7/72.9 ± 9.3 for auscultation (difference of −3.3 ± 7.3/0.9 ± 6.1; p-values < 0.0001 for systolic and 0.17 for diastolic). The proportion of devices with systolic or diastolic BP differences from auscultation of 5, 10 and 15 mmHg or greater was 69%, 29% and 7%, respectively. Increasing arm circumference was a statistically significant predictor of higher systolic (parameter estimate 0.61 per cm increase; p-value 0.004) and diastolic (0.38; 0.03) BP. Conclusions: Although mean differences from two-observer auscultation were acceptable, when tested on their owners, most home BP devices were not accurate to within 5 mmHg. Ensuring acceptable accuracy of the device-owner pairing should be prioritized.